An ecological assessment of Foul and Folly Bays, Morant wetlands area, Jamaica using Ecopath with Ecosim. (March 2015) - Webber, Mona; Persad, Gale; Harris, Nicole; Wilmot, Inilek; Webber, Dale
Abstract: The Morant wetlands bays (Foul and Folly Bays) are contiguous with the Great Morass, a large wetland located at the extreme eastern end of the island of Jamaica. A multidisciplinary ecological assessment of the bays was conducted from April 2007–May 2008 aimed at generating a baseline of conditions to confirm the trophic status and importance of the area thus providing support for its designation as a protected area. Water column assessment included zooplankton and phytoplankton collections for 12 months at 11 stations. Zooplankton tows were conducted using a 200 μm net (0.5 m hoop diameter) contemporaneous with 5 l Niskin bottle casts for phytoplankton. Zooplankton abundances were determined for nine functional groups (calanoids, cyclopoids, harpacticoids, nauplii, copepodites, carnivores: medusa and chaetognaths, larvaceans and larvae) for which equivalent biomass was generated using conversion factors based on previous studies in Jamaica. Total phytoplankton biomass (mg Chl a m −3 ) was determined directly using filtration (onto a 0.7 μm filter) and fluorometry while detritus was estimated using the model. Ecopath with Ecosim 5.1 was then used to model the trophic interactions of the planktonic community in the Morant wetlands bays. 116 different taxa of zooplankton were identified with a mean total abundance ranging from 282 ± 56 to 3459 ± 752 animals m −3 across the annual cycle. Total phytoplankton biomass (Chlorophyll a ) ranged from 0.14 ± 0.04 to 0.34 ± 0.2 mg m −3 across the annual cycle. A similar study in a pristine bay (Discovery Bay) on the north coast of Jamaica indicated mean zooplankton abundances between 1077 ± 191 and 3794 ± 87 animals m −3 and phytoplankton biomass between 0.4 and 0.8 mg m −3 . The plankton parameters suggest that Foul and Folly Bays are even more pristine than Discovery Bay and the Ecopath model indicated that unlike Discovery Bay, these Morant wetlands bays were far more resilient and therefore able to recover from stresses (e.g. eutrophication). However, there is still need for protection of this pristine area as the high abundance of larvae coupled with fast flowing currents through the bays provides evidence that this area could be an important source of larvae to other areas of Jamaica's south coast. Highlights: An assessment of the eutrophication status of Morant wetlands bays is presented. Ecopath with Ecosim 5.1 is used to model trophic interactions of the plankton. Results indicate that the bays are pristine and an important source of larvae. Ecopath model indicates the bays are resilient and able to recover from stresses.